Almond supplementation reduces serum uric acid in coronary artery disease patients: a randomized controlled trial. Issue 1 (December 2015) - Jamshed, Humaira; Gilani, Anwar-ul-Hassan; Sultan, Fateh; Amin, Faridah; Arslan, Jamshed; Ghani, Sumaira; Masroor, Madiha
Abstract Objective Elevated serum uric acid (UA), a biomarker of renal insufficiency, is also an independent prognostic marker for morbidity in coronary artery disease (CAD) and poses serious health risks. This study reports the effect of almond consumption on UA in CAD patients. Study design A randomized controlled clinical trial was conducted with three groups: no-intervention (NI), Pakistani almonds (PA) or American almonds (AA). Patients were recruited from the Cardiology Clinics, Aga Khan University Hospital. Two follow-ups were scheduled at week-6 and week-12. 150 patients were randomly divided in three groups (50 per group). NI was not given almonds, whereas the PA and AA were given Pakistani and American almond varieties (10 g/day), respectively; with instruction to soak overnight and eat before breakfast. Results Almonds supplementation significantly reduced (p  < 0.05) serum UA among groups, and over time. At week-6, UA concentrations were -13 to -16 % less in PA and AA; at week-12 the concentrations were -14 to -18 % less, compared to NI. Systolic and diastolic blood pressure and body weights of the participants remained fairly constant among all the groups. Conclusion Almonds (10 g/day), eaten before breakfast, reduces serum UA in CAD patients. Prevention of hyperuricemia can confer protection from kidney and vascular damage and if extrapolated for general population, dietary almonds can offer grander health benefit. Trial is registered at Australian New Zealand Clinical trial registry as ACTRN12614000036617.